MATHEMATICAL ANALYSIS OF INFLOW PERFORMANCE FOR MULTIPHASE FLOW RESERVOIRS - Temitayo Sheriff Adeyemi,; Hafis Olamilekan Wahab,; Juliana Omotayo, (International Journal of Innovations in Engineering Research and Technology, 2023)
The importance of Inflow Performance Relationship (IPR) models to the oil and gas industry cannot be over-emphasized. IPR models are very essential in predicting future production from hydrocarbon reservoirs. Accurate prediction of future production from hydrocarbon reservoirs is very essential as it influences field’s viability and economic analysis. For years, attempts had been made by many authors to develop models suitable for this purpose. However, they have not been so successful as most the developed models have been found wanting in accuracy. Hence, there is a need for improved and accurate models. Therefore, the objective of this research is to introduce IPR models that can be used to predict production from hydrocarbon reservoirs with high degree of confidence. The pseudo-steady state solution of the Partial Differential Equation (PDE) governing multiphase flow in homogenous and isotropic porous media was obtained via Laplace Transform. Furthermore, the obtained solution was expanded using Taylor’s series expansion method in order to obtain a form that is suitable for forecasting production from hydrocarbon reservoirs. By considering different number of terms in the Taylor’s series form of the solution, five different Inflow Performance Relationship (IPR) models were obtained. Furthermore, performance analysis was carried out using statistical metrics to ascertain the reliability of the developed models. The result of this analysis shows that the developed models perform better than Vogel and Wiggins models, the two widely celebrated models in the oil and gas industry.